2019
DOI: 10.3390/sym11050663
|View full text |Cite
|
Sign up to set email alerts
|

Irreversibility Analysis of Hybrid Nanofluid Flow over a Thin Needle with Effects of Energy Dissipation

Abstract: The flow and heat transfer analysis in the conventional nanofluid A l 2 O 3 − H 2 O and hybrid nanofluid C u − A l 2 O 3 − H 2 O was carried out in the present study. The present work also focused on the comparative analysis of entropy generation in conventional and hybrid nanofluid flow. The flows of both types of nanofluid were assumed to be over a thin needle in the presence of thermal dissipation. The temperature at the surface of the thin needle and the fluid in the free stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…Rasool et al [6,7] reported on some interesting findings in Marangoni convection of nanofluids involving simple as well as Riga plates with various other important physical parameters, respectively. Some recent and interesting articles can be found in [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and cross references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…Rasool et al [6,7] reported on some interesting findings in Marangoni convection of nanofluids involving simple as well as Riga plates with various other important physical parameters, respectively. Some recent and interesting articles can be found in [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and cross references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…Due to some parts of the pump rotating, as well as the whole shape being axially symmetric, the monitor points were set to rotate with the impeller in the rotation parts. Afridi et al [18] carried out an irreversibility analysis of hybrid nanofluid flow over a thin needle with the effects of energy dissipation. When conducting the theoretical study of the heat transfer and entropy generation in the flow of dissipative hybrid nanofluid, the coordinate system and the geometry of the physical flow model are only shown for half of the thin needle, because of its symmetry, which simplified the calculation process of this study.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting nonlinear coupled equations were solved employing optimal homotopy analysis method and gave report on the evolution of the quantities of interest with the involved parameters. A comparative study on the irreversibility of a conventional nanofluid and a hybrid one with viscous dissipation was carried out in Afridi et al In that study, the nanofluids were assumed flowing over a thin needle and the equations were tackled via an in‐built MATLAB algorithm, such as RKF45. The flow of blood through a curved vessel having stenosis and aneurysm was examined numerically in Sultan et al It should be pointed out that the blood rheology has been estimated by shear‐thinning behavior of non‐Newtonian Eyring–Powell fluid model.…”
Section: Introductionmentioning
confidence: 99%